2007
DOI: 10.1128/aem.02622-06
|View full text |Cite
|
Sign up to set email alerts
|

Diversity, Activity, and Abundance of Sulfate-Reducing Bacteria in Saline and Hypersaline Soda Lakes

Abstract: Soda lakes are naturally occurring highly alkaline and saline environments. Although the sulfur cycle is one of the most active element cycles in these lakes, little is known about the sulfate-reducing bacteria (SRB). In this study we investigated the diversity, activity, and abundance of SRB in sediment samples and enrichment cultures from a range of (hyper)saline soda lakes of the Kulunda Steppe in southeastern Siberia in Russia. For this purpose, a polyphasic approach was used, including denaturing gradient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
144
0
5

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 214 publications
(155 citation statements)
references
References 33 publications
6
144
0
5
Order By: Relevance
“…The rates were comparable with previous measurements (Foti et al 2007) and, in general, corresponded to characteristic values of eutrophic marine sediments (Lein et al 2002). Salinity seems to have no effect on the sulfate reduction process in the studied soda lakes.…”
Section: Sulfate-reducing Activitysupporting
confidence: 91%
See 1 more Smart Citation
“…The rates were comparable with previous measurements (Foti et al 2007) and, in general, corresponded to characteristic values of eutrophic marine sediments (Lein et al 2002). Salinity seems to have no effect on the sulfate reduction process in the studied soda lakes.…”
Section: Sulfate-reducing Activitysupporting
confidence: 91%
“…In the last decade, special attention has been given to the investigation of the microbial communities in soda lakes using both traditional isolation methods (Duckworth et al 1996;Sorokin et al 2004;Sorokin and Kuenen 2005b) and molecular biology techniques (Humayoun et al 2003;Rees et al 2004;Scholten et al 2005;Foti et al 2007). Few reviews (Zavarzin et al 1999;Jones et al 1998) summarize these results, showing that soda lakes contain representatives of the major trophic and phylogenetic groups of prokaryotes, and that they can be considered as autonomous systems, in which cycling of nutrients is close to complete.…”
Section: Introductionmentioning
confidence: 99%
“…The culture medium was inoculated with a mixture of sediments from hypersaline soda lakes in South-Western Siberia (Altai, Russia). The description of the sediments is given elsewhere (Foti et al 2007). Development of the culture was followed by the monitoring of thiosulfate consumption.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, the cultivation dependent and independent analyses of planktonic and sediment microbial communities include, among others, studying the soda lakes of South-East Siberia, Russia (Foti et al 2007(Foti et al , 2008, North-East Mongolia (Sorokin et al 2004), Inner Mongolia, China (Zhang et al 2001;Ma et al 2004a), Lonar Lake, India (Wani et al 2006;Joshi et al 2008), the East African Rift Valley, Kenya and Tanzania (Rees et al 2004;Mwirichia et al 2010Mwirichia et al , 2011, Wadi An Natrun, Egypt (Mesbah et al 2007), as well as Mono Lake, California, USA (Hollibaugh et al 2001;Humayoun et al 2003) and Soap Lake, Washington, USA (Dimitru et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Sequences related to thiosulfate-reducing species of Dethiosulfatibacter aminovorans and Fusibacter paucivorans as well as the sulfate-reducing species Desulfobotulus sapovorans and Desulfonatronum lacustre were also found among the Böddi-szék clones. In previous studies, the presence of sulfate-reducing phylotypes was reported mainly from the sediment of saline and soda lakes (Foti et al 2007(Foti et al , 2008Mesbah et al 2007). …”
mentioning
confidence: 98%